Upaya Meningkatkan Kemampuan Guru Sma Negeri 1 Tapung Hilir, Kabupaten Kampar Provinsi Riau Dalam Memanfaatkan Akun Belajar.Id Yang Terintegrasi Dengan Google Workspace For Education Melalui Workshop Penggunaan Teknologi Informasi Pada Kegiatan Pembelajar - sarpiati (Universitas Lancang Kuning, 2022)
Teachers at SMA Negeri 1 Tapung Hilir rarely know how to use a learning.id account with Google Workspace for Education. Researchers often find teachers struggling to use this information technology devices and asking for support from other teachers. Thus, a teacher's inability to use technology negatively impacts the learning process. To improve teachers' ability to use a learning.id account that is integrated with Google workspace for education, a workshop on the use of information technology in activities and learning will be held in 2020/2021. After the action research, data revealed an increase in teachers' ability to use their learning.id accounts. In cycle 1, instructors' capacity to use the learning.id account, which was connected with Google Workspace for Education, increased significantly. The findings of teacher-led exams on the usage of information technology show this trend. In the test, 26 (86.67%) got the predicate